KONSEP DESAIN TAMAN KETETANGGAAN SEBAGAI KATALIS BAGI LINGKUNGAN BERKELANJUTAN - Izzati, Husna; Aditya, Krisna (Universitas Mercu Buana, 2024)
The perspective of human relations with nature is understood as a reciprocal relationship that should be mutually beneficial.However, humans often only act, appreciate and protect it after the natural environment is difficult to obtain or access. As a follow-up to environmental sustainability efforts, the SDGs concept is applied to sustainable architectural design, one of which is in the development of parks in urban areas. Neighborhood parks are a type of green open space that are often found in residential areas in the city of Bandung.Despite its insignificant size, neighborhood parks are able to play a greater role in influencing the surrounding environment both from an ecological, economic and social interaction perspective.However, the existence of these parks does not necessarily indicate the existence of an environmental sustainability concept.This research intends to examine what design concepts influence the environment, and the extent to which this influence has an impact on environmental sustainability.Using descriptive qualitative methods with main data from observation and literature review, it is hoped that it will be able to provide a complete, systematic picture and provide an appropriate interpretation of existing facts.The case example takes two neighborhood parks located in the city of Bandung, namely Superhero Park and Arcamanik Endah Park, which were selected based on several criteria including accessibility factors, area size, public facilities and services, and post-pandemic development factors that show positive trends towards sustainability environmental aspects.From the observations, it was found that there were indications of the design concept as a catalyst which showed an influence on the sustainability of the surrounding environment